Ca OXALATES IN LICHEN GENUS CLADONIA ON DUMPS OF THE SUGUR COPPER DEPOSIT (SOUTH URALS) - E.E. Artemenko; M.A. Rassomakhin; P.V. Khvorov; K.A. Filipрova (Минералогия)
Ca oxalate crystals (mainly, weddellite (Ca(C2O4) • (2.5-x)H2O) are found in the lichen Cladonia chlorophaea on dumps of the Sugur copper deposit underwent to aerosol emissions from the Karabash copper smelting (KCS), South Urals. The samples of lichens and substrate are studied by scanning electron microscopy, energy-dispersion microanalysis, X-ray phase analysis and inductively coupled plasma mass spectrometry. The contents of toxic elements (Cu, Zn, Pb, Cd, Sn, Sb, Se, As, Te) of substrate and lichen thalli exceed their average contents in the Earth’s crust, whereas their contents in thalli are lower than in substrate (except for Cd). The high Pb content is associated with Ca oxalate. The lichen thalli contains inclusions of minerals, which compose the dump, and spherical particles, which are associated with the activity of the KCS and which contain significant concentrations of heavy metals.